Social and financial performance of MFIs: complementary or compromise?. Issue 1 (23rd November 2020) - Navin, Nitin; Sinha, Pankaj
Abstract : Purpose: With the ongoing transformation of the microfinance sector, questions have been raised on the ability of microfinance institutions (MFIs) to perform financially well without compromising with their social objectives. The current study attempts to analyse the social and financial performance of Indian MFIs with an objective to find the kind of relationship between these two objectives. Design/methodology/approach: The dynamic framework of simultaneous equations model is used to find the nature of the relationship which exists between social and financial performance of Indian MFIs. Findings: The study finds that depth of outreach enables MFIs to achieve financial sustainability. On the other hand, financially strong MFI lend more as reflected by an increase in their average loan size. Research limitations/implications: Many MFIs still receive subsidies to support their operations. Ideally, adjustments should be made to remove the effect of such subsidies on their cost. However, due to non-availability of data, the study fails to make any adjustment for the subsidies. Practical implications: The presence of a complementary relationship between social and financial performance in the Indian microfinance sector is quite encouraging for the policymakers during the current time when the sector is becoming less dependent on subsidies. However, the recent upsurge in the average loan size requires attention. Social implications: The findings suggest that MFIs can achieve financial sustainability while targeting poor clients. This indicates that MFIs can perform socially good along with their financial performance. Originality/value: Such study is vital when the Indian microfinance sector is moving away from subsidies to become self-reliant and commercialised. Few studies have focused on this aspect of Indian microfinance sector.